NILAI KESEHATAN DAN WORD OF MOUTH TERHADAP SIKAP, PERILAKU, DAN INTENSI PEMBELIAN KONSUMEN - Tanugraha, Alvian; Haryanto, Jony Oktavian (Journal of Management and Business, 2012)
One of the most dangerous illnesses which are often ignored by Indonesian people is Osteoporosis. On the one hand, many people start to be aware with this illness. On the other hand, most of the Indonesian society does not pay attention to this issue. Marketers see this illness as a big opportunity. As a result, it could be seen that there are a lot of functional foods, especially for healthyness were developed by companies. This research uses one of the most popular brand in Indonesia, Anlene as an experiment objects considering that Anlene serves the specific market in the healthy food. This research identifies the effect of health value to attitudes toward functional foods and attitudes toward the product. Furthermore, this research aims to acknowledge the effect of attitudes toward functional foods toward perceptions of healthiness and hedonic expectations. This research would also identify the effect of perceptions of healthiness, hedonic expectations, and word of mouth to purchasing intention. There are 8 hypotheses that would be tested and analyzed using SEM software LISREL 8.8.